قياس جاهزية الصحة الالكترونية في الدول النامية: مراجعة للأدبيات - بن سعيد مراد; زقاغ عادل; بخوش سامي (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تهدف هذه الدراسة إلى عرض وتحليل للأدبيات حول موضوع قياس جاهزية الصحة الالكترونية في الدول النامية. وعليه، سوف نقوم بمراجعة لنماذج تقييم الجاهزية الإلكترونية لخدمات الرعاية الصحية بشكل عام ومدى علاقتها ببيئة الدول النامية، ثم نقوم بعرض ثلاثة نماذج ذات مصداقية في مجال قياس وتقييم جاهزية الصحة الالكترونية في الدول النامية. وقد توصلت الدراسة إلى أن الدراسات والبحوث التي تختص بتوفير مقاييس وادوات لقياس جاهزية الصحة الالكترونية في الدول النامية مازالت لا تلبي الحد الأدنى، وتبقى قاصرة على توفير صيغ توافقية خاصة ببيئة كل الدول النامية. This study aims to present and analyze the literature on the subject of measuring e-health readiness in developing countries. Accordingly, we will review models for assessing the e-readiness of health care services in general and their relationship to the environment of developing countries, and then we will present three credible models in the field of measuring and evaluating e-health readiness in developing countries. The study concluded that studies and researches concerned with providing standards and tools to measure e-health readiness in developing countries still do not meet the minimum, and remain limited to providing consensus formulas specific to the environment of all developing countries.